METAFORA DALAM PUISI KARYA CHAIRIL ANWAR - Subagiharti, Heni; Handayani, Diah Syahfitri; Adawiyah, Murni (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study analyzes the metaphors in Chairil Anwar's poetry, which aims to (1) find out what metaphors are contained in Chairil Anwar's poetry. (2) To find out the metaphors in the poetry by Chairil Anwar. (3) To find out the reason the author uses the metaphor in his poem. The method used in this research is descriptive analysis method. Descriptive analysis is used to get a careful description of the contents of the poem. The results of this study show that the metaphor contained in Chairil Anwar's poetry describes how deep human "surrender" is to God. However, I lyric in the poem is described as calmer and more mature in dealing with everything, including when he has to face death. This poem can teach that in fact no matter how hard we try or work, all paths of life and decisions are in His hands. The metaphorical meaning that Chairil Anwar reveals in his poetry is that the metaphor of defeat is very interesting to show; defeat is a symbol of surrender and is very thick with the smell of death. Poets use these words to compare things, that something is called the meaning of metaphor. The author uses metaphor in his poetry to compare things directly. Blooming roses and jasmine represent something beautiful and attractive. The metaphor used by the poet to describe the closeness between the poet and God in praying and relating to God. Keyword: Metaphor, Poetry, Chairil Anwar Abstrak: Penelitian ini menganalisis metafora dalam puisi Chairil Anwar yang bertujuan untuk (1) mengetahui metafora apa saja yang terdapat dalam puisi Chairil Anwar. (2) Untuk mengetahui metafora yang terdapat dalam puisi karya Chairil Anwar. (3) Untuk mengetahui alasan pengarang menggunakan metafora dalam puisinya. Metode yang digunakan dalam penelitian ini adalah metode analisis deskriptif. Analisis deskriptif digunakan untuk mendapatkan gambaran yang cermat tentang isi puisi. Hasil penelitian ini menunjukkan bahwa metafora yang terdapat dalam puisi Chairil Anwar menggambarkan betapa dalamnya “penyerahan” manusia kepada Tuhan. Namun, I lirik dalam puisi tersebut digambarkan lebih tenang dan lebih dewasa dalam menghadapi segala hal, termasuk ketika harus menghadapi kematian. Puisi ini dapat mengajarkan bahwa sesungguhnya sekeras apapun kita berusaha atau bekerja, segala jalan hidup dan keputusan ada di tangan-Nya. Makna metafora yang diungkap Chairil Anwar dalam puisinya adalah bahwa metafora kekalahan sangat menarik untuk ditampilkan; kekalahan merupakan simbol penyerahan diri dan sangat kental dengan aroma kematian. Para penyair menggunakan kata-kata ini untuk membandingkan sesuatu, sesuatu itu disebut makna metafora. Pengarang menggunakan metafora dalam puisinya untuk membandingkan sesuatu secara langsung. Bunga mawar dan melati yang mekar melambangkan sesuatu yang indah dan menarik. Metafora digunakan penyair untuk menggambarkan kedekatan antara penyair dan Tuhan dalam berdoa dan berhubungan dengan Tuhan. Kata kunci: Metafora, Puisi, Chairil Anwar